(untitled) (LAPAI JOURNAL OF NIGERIA HISTORY, 2024)
This paper examines the role of Baro Niger River Port in the development of inland waterways transport in colonial Northern Nigeria between 1900 and 1960. The Port’s strategic location on the Niger River made it a critical hub for the transportation of goods and materials. Using both primary and secondary sources derived from archival documents, oral interviews, books, dissertations and theses, the study finds that the construction of Baro Port and its adjoined railway line solidifies the transport system on the inland waterways in Nigeria. The paper argues that despite the increasing concentration on other modes of transport systems among other challenges, the port was a significant point for the import of European-made goods, and export crops such as groundnut, cotton, and palm oil, through to the end of British rule in Nigeria. Therefore, this paper contributes to the understanding of the history of inland waterways transport by highlighting the important role Baro Port played in the economic history of colonial Nigeria.